Control mechanism and directions for state regulation of transaction costs - Galyna Kolisnyk (Cхід, 2016)
The paper looks into a control mechanism and identifies some directions for state regulation of transaction costs, which comprise the following: a) summary of a range of program activities; b) determination of a goal and operational goals for development of a control system structure for transaction costs; c) improvement of the regulatory support of the dominant directions for minimization of transaction costs; d) decrease of a level of costs associated with transfer of ownership and overcoming of information non-transparency; e) strengthening the infrastructure support of state policy of transaction costs reduction. The author groups together those factors which influence the generation of transaction costs, examines the components of the economic freedom index and the dynamics of Heritage Foundation's transaction costs indicators in Ukraine in 2005-2016. The indicators of Ukraine are compared in the Doing Business rating over a period up to 2015-2016.